Pemanfaatan Photonovela untuk Peningkatan Kesiapsiagaan Bencana Anak Usia Sekolah - Rachmalia Rachmalia; Sri Intan Rahayuningsih; Hasmila Sari; Imelda (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2026)
School-age children are vulnerable to disaster threats, including those in the school environment. It is important to recognize and understand their daily surroundings. Using photonovella is an innovative strategy. Photonovella helps reconstruct children's understanding and awareness of disaster preparedness. They also help communicate experiences and select which stories to tell. The objective is to help school-aged children recognize disaster risks and build disaster preparedness using a photonovella. The project results show improved attitudes and awareness in identifying disaster risks and better planning of prevention efforts. Photonovella are attractive and easy for children to understand. They serve as an effective medium for disaster preparedness education in schools. Involvement from teachers is recommended for success and sustainability.